2014
DOI: 10.1039/c3tb21837f
|View full text |Cite
|
Sign up to set email alerts
|

Tunable functionality and nanogeometry in tetrahydrofuran hydroperoxide and 3-aminopropyl-trimethoxysilane mediated synthesis of gold nanoparticles; functional application in glutathione sensing

Abstract: We report herein a process involving the active role of tetrahydrofuran hydroperoxide and 3-aminopropyltrimethoxysilane that allows controlled synthesis of functional gold nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…The properties of as synthesized PdNPs and bimetallic nanoparticles (as shown in Fig. 1) are analogous to that reported earlier [24,26,35,36] justifying novelty of the present process for rapid and controlled synthesis of these nanoparticles under ambient conditions. The time taken during such nanoparticle formation lie between 5 min to 2 h validating the use of 3-APTMS and THF-HPO as most efficient reagents in the synthesis of noble metal nanoparticles and bimetallic nanoparticles.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The properties of as synthesized PdNPs and bimetallic nanoparticles (as shown in Fig. 1) are analogous to that reported earlier [24,26,35,36] justifying novelty of the present process for rapid and controlled synthesis of these nanoparticles under ambient conditions. The time taken during such nanoparticle formation lie between 5 min to 2 h validating the use of 3-APTMS and THF-HPO as most efficient reagents in the synthesis of noble metal nanoparticles and bimetallic nanoparticles.…”
Section: Resultssupporting
confidence: 84%
“…When gold salt was replaced by tetrachloropalladate, it has been found that THF-HPO on mixing with 3-APTMS capped Pd 2+ ions immediately converted into a light yellow solution which subsequently leads into black color PdNPs sol. The role of 3-APTMS and THF-HPO has been examined and the observations based on TEM and AFM analysis justify the similar behavior as that recorded for the synthesis of AuNPs [26]. In addition to that the process also enables the synthesis of bimetallic nanoparticles of palladium and gold of variable ratio under two different conditions of reacting system: (a) simultaneous and (b) sequential.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…In addition to that some of such functional alkoxysilanes like 3-aminopropyltrimethoxysilane (3-APTMS) and 3-glycidoxypropyltrimethoxysilane (3-GPTMS)) have recently been utilized as reagents and stabilizer during the synthesis of noble metal nanoparticles under ambient [10][11][12]. Further the active role of 3-APTMS has also been demonstrated during the synthesis of prussian blue nanoparticles (PBNPs) [13,14].…”
Section: Introductionmentioning
confidence: 99%